Bandwidth controlled antenna for lte applications - Obadiah, Ali Nyangwariman (2014)
Reconfigurable antennas have generated a lot of interest lately due to evolving technologies which require reconfigurable frequency, bandwidth, radiation pattern and polarization in communication systems. Wideband to narrowband frequency reconfigurable antennas are needed for communication systems which require differing amounts of bandwidth such as LTE. The aim of this project is to design an antenna suitable for bandwidth control at LTE frequency based on the differing bandwidth requirements of LTE. A new concept of a reconfigurable bandwidth controlled antenna is proposed. The structure used is a taper slot Vivaldi antenna with wideband capability, moderate high gain and symmetrical E and H planes. The Vivaldi is integrated with two pairs of resonator rings along the elliptically shaped taper slot line to achieve bandwidth control. The resonator rings are switched ON or OFF with the aid of switches to yield a wideband frequency of 1 to 3 GHz and two narrower frequencies with different bandwidths at 2.6GHz. The simulation results are done in CST microwave studio. The measured and simulated results showed a good agreement. The fabricated antenna is suitable for use in bandwidth controllable applications such as in Long Term Evolution which functions based on OFDMA modulation techniques which support differing amounts of bandwidth